Earthworm Diversity and Distribution in Kathmandu, Bagmati Province, Central Nepal - Singh, Ankit Kumar (International Journal of Applied Sciences and Biotechnology, 2022)
Earthworms are of ecological and economic significance and are directly related wit human health through biogeochemical cycle. Such a valuable faunal group needs immediate intensified taxonomic treatment in Nepal for their sustainable use, efficient commercial production and biodiversity conservation. Systematic random sampling was used for site selection and hand sorting method was used for sample collection from the field. Collected specimen were photographed in field and preserved in ethanol for lab study with tagging. In total, study reported eight species belonging to two families Lumbricidae and Megascolecidae. External morphological features helped on identification and taxonomic key preparation. Among two sites 6 species were common and abundantly recorded from almost habitats whereas, 1/1 species were different in each site with uncommon reporting from harsh environment. Cultivated crop land with litter and compost was known to be more diverse in species richness than other habitats. Detail taxonomic study and distribution mapping is an essential for Earthworms in Nepal to complete the global database and national soil engineer documentation for organic and healthy environment. Int. J. Appl. Sci. Biotechnol. Vol 10(2): 124-133.